Computational analysis of two dimensional flows on a convertible car roof - Abdullah, Muhamad Nawi (2013)
This project describes the study of computational analysis of two dimensional flows on convertible car roof. The objectives of this study are to analyze and study the effect of pressure coefficient (Cp) and Drag Coefficient (Cd) on convertible car roof. The structure of model of convertible car roof was modelled using Solidworks software and analysis was performed using Ansys software. In this experiment, four model car convertible roofs were developed through Solidworks software based on the ratio of 1:20 of the original size of the vehicle. Then the four models tested in three different wind tunnel to get the best results and very similar to the real situation. The task was done by using Computational Fluid Dynamic (CFD) analysis for expected vehicle speed of 120 km/h. A pressure and drag force was obtained based on inputs from CFD analysis. This pressure and force was used to calculate the pressure coefficient and drag coefficient of the model as a whole. Results showed that the model C has the best compared with other models where the minimum and maximum pressure coefficients for model C is the lowest compared to other models of -0.9267 and 0.0488. While the drag coefficient is 0.6526 for model C. Surface design and roof arches were found to affect the results of this experiment.